DETERMINASI KEMISKINAN DAN PENGANGGURAN DI INDONESIA - Nurhayati Nurhayati; Sri Yani Kusumastuti (Media Ekonomi, 2020)
It is generally seen that the number of poor people tends to decrease, and the unemployment rate also tends to decrease slowly, but economic growth has decreased. Therefore, this study wants to look at the factors that influence poverty and unemployment in Indonesia during the 2014-2018 period. The object of the research is to take a case in Indonesia using panel data which is a combination of time series data and cross section, where time series data are from 20014-2018 and cross sections are 33 provinces in Indonesia. The analytical tool used to answer the problems raised in this study is the Linear Data Panel Regression. The first step to do is to issue estimation results, namely Common Effect Model, Fixed Effect Model, and Random Effect Model. The second stage is to choose the model using the Chow Test, Hausman Test and LM Test. The third stage is to analyze the magnitude of the coefficient, coefficient sign, significance test and goodness of fit test (coefficient of determination and Global Test). The test results show that the unemployment model uses alpha 10%, there are variables that have negative effects such as WAGE and Health, while RGDP, POP and EDUC have no statistical effect. The poverty model shows that of the five variables proposed in influencing the level of open unemployment at an error rate of 10% are RDGP, WAGE, EDUC and HEALTH while POP has no statistical effect. The final model shows statistically at a 10% error rate there is a positive influence on the level of open unemployment that has been influenced by RGDP, POP, WAGE, EDUC and HEALTH on poverty levels in Indonesia.